Medulloblastoma and ABO-Rh Blood Group: Evidence of an Association between the Distribution of Blood Group Antigens and Medulloblastoma - Bajaj, Ankur; Ansari, Rehana; Jaiswal, Somil; Srivastava, Chhitij; Ojha, Bal Krishna; Rizvi, Imran; Chandra, Tulika (Indian Journal of Neurosurgery, 2023)
Objective Medulloblastoma is the most common central nervous system embryonal tumor and the most common malignant brain tumor of childhood. This study aims to find out the incidence of the ABO-Rh blood group in medulloblastoma patients of northern India to assess the utility of the blood group as a preclinical non-modifiable risk factor.Materials and Methods The study cohort consisted of 87 pediatric patients (age up to 18 years) who were diagnosed after histopathological examination with medulloblastoma at a university hospital in Lucknow between 2014 and 2019. Hundred random pediatric individuals from the same population who were admitted to the same hospital between 2014 and 2019 for non-tumor cases were selected as the control group. Data concerning characteristics including age, sex, ABO blood group, and Rh factor were collected from hospital records. The distribution of ABO-Rh blood groups in the study population was compared with the general population using the χ2 test. Statistical analysis of the ABO-Rh blood groups in the study population was done using the IBM SPSS statistics version 24.0.Results Data analysis revealed that blood group A was significantly associated with medulloblastoma cases (odds ratio [OR] = 2.93; 95% confidence interval [CI]: 1.35–6.34). We find that the classical subtype was prevalent with the blood group A (43.8%), while the desmoplastic subtype was associated with the blood group O (38.5%).Conclusion Blood group A has a higher risk for the development of medulloblastoma while blood group O has the least risk. These findings suggest that blood group antigen should be considered as a non-modifiable preclinical risk factor for developing medulloblastoma.
Keywords: medulloblastoma; ABO-Rh; blood groups antigens